High occurrence of postintensive care syndrome identified in surgical ICU survivors after implementation of a multidisciplinary clinic. Issue 2 (August 2021) - Bottom-Tanzer, Samantha F.; Poyant, Janelle O.; Louzada, Maria T.; Ahmed, Sana E.; Boudouvas, Abbey; Poon, Eileen; Hojman, Horacio M.; Bugaev, Nikolay; Johnson, Benjamin P.; Van Kirk, Anna Lisa; Daniel, Eryn; Emoff, Caroline; et al.
Abstract : BACKGROUND: Postintensive care syndrome (PICS) has been identified in a large proportion of medical intensive care unit survivors; however, the occurrence surgical intensive care unit (SICU) survivors is unknown. We implemented a multidisciplinary critical care outpatient clinic (CCOC) to identify the occurrence of PICS in SICU survivors. METHODS: Seventy acute care surgery and trauma patients, 18 years or older, who remained in the SICU for 72 hours or longer at a Level I trauma center were seen in CCOC at 2 weeks, 12 weeks, and 24 weeks after hospital discharge. The CCOC staffing included a nurse coordinator, social worker, critical care pharmacist, physical therapist, and acute care surgeon who identified PICS sequelae in their respective specialties by clinical criteria and screening questionnaires. RESULTS: Of 82 eligible patients, 70 (85.4%) were seen at least once for 116 total visits. Forty-three (61.4%) patients suffered traumatic injuries and 27 (38.6%) underwent emergent general surgery. Sixty-seven (95.7%) demonstrated at least one PICS criterion. Over all visits, 26 (37.1%) patients presented with one PICS criterion, 24 (34.3%) patients with two, and 17 (24.3%) with three. Cognitive impairment was observed in 29 (41.4%) patients, psychiatric in 30 (42.9%), and physical symptoms in 65 (92.9%). Activity Measure for Post-Acute Care scores improved from severe impairment at admission to full function by 12 weeks postdischarge, yet 6 Minute Walk Test scores remained below age-matched references through all visits. Patients expressed mild to moderate depression based on Patient Health Questionnaire-9 scores. A medication reconciliation was completed at 96.5% (112/116) of the visits with 116 total medication recommendations. By 24 weeks following discharge, only 26.4% (14/53) of previously employed patients had resumed work. CONCLUSION: Through the successful implementation of a multidisciplinary CCOC, this study identifies an exorbitant rate of PICS among SICU survivors. LEVEL OF EVIDENCE: Therapeutic/epidemiological, level III.